Records Committee review for rare bird sighting of Lesser Black-backed Gull at Coralville Reservoir, 1991 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1991)
Records Committee for a Lesser Black-backed Gull at Coralville Reservoir in Johnson County, IA on November 28, 1991. Includes a record review document with votes and a documentation form submitted to the committee. Epson - sheet feed